PELATIHAN SCRAPBOOK ART SEDERHANA BERTEMA ALAM UNTUK MENINGKATKAN KETRAMPILAN MOTORIK HALUS ANAK - Enis Fitriani; Tisa Maharani; Marsuki Marsuki (JPM PAMBUDI, 2021)
Fine motor skills are needed by early childhood considering that fine motor skills are one part of the stages of child development. The objectives to be achieved in this Community Service program were to provide information, provide understanding, and provide experience in making scrapbook art to improve the fine motor skills of children at RA Sirrul Khuluq, Malang Regency. The target in this program was the teachers. This program had been carried out in the form of training where teachers get information or theories about scrapbooking and fine motor skills in children in general and provide understanding and experience about simple and interesting scrapbook art suitable for children with appropriate natural themes. It can be concluded that this community service activity has been successfully proven by the enthusiasm of the teachers to ask questions, share experiences, discussion, and participate in scrapbooking.